E-government learning media through augmented reality technology - Yusuf, Muhammad; Sophan, Mochammad Kautsar; Muntasa, Arif; Alamsyah, Nurwahyu; Nakkas, Haythem; Sari, Putri Pradnyawidya (Association for Scientific Computing Electrical and Engineering, 2020)
Augmented reality (AR) is one of the newest learning technologies besides Artificial Intelligent, Virtual Reality, Virtual World, Alternates Reality Games, and Wearable Computing. E-Government is becoming an evolving academic field and transforming to be E-Governance, E-Participation, E-Service, E-Democracy, E-Voting issues. Therefore, some universities have E-Government course in their curriculum. AR can be one of the learning media to learn and teach E-Government effectively and interestingly. This research aims and contributes to develop a novel model of E-Government learning media using AR. Furthermore, this work has three novelties as follows:First, a method to develop e-Government learning media using AR. Second, a novel model of e-government learning media based on augmented reality technology. Third, the material courses are command centre and public service mall materials based in Surabaya, Indonesia. The new model of learning media using AR consists of main components, i.e., user, devices, AR, and course materials. Additionally, this novel model has some sub-components, such as AR object, marker, text, image, audio, video, and 3D animation. The proposed model has some practical and theoretical implications. For the theoretical implication , it adds a model of learning media for e-government course and extends the body of knowledge for e-government and augmented reality fields. For practice, e-Government courses can uilize the augmented reality application.